2016
DOI: 10.1007/s11336-016-9527-8
|View full text |Cite
|
Sign up to set email alerts
|

Extending multivariate distance matrix regression with an effect size measure and the asymptotic null distribution of the test statistic

Abstract: Person-centered methods are useful for studying individual differences in terms of (dis)similarities between response profiles on multivariate outcomes. Multivariate distance matrix regression (MDMR) tests the significance of associations of response profile (dis)similarities and a set of predictors using permutation tests. This paper extends MDMR by deriving and empirically validating the asymptotic null distribution of its test statistic, and by proposing an effect size for individual outcome variables, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 44 publications
2
59
2
Order By: Relevance
“…All libraries were included in this analysis, without any filter, since even libraries that do not share any locus provide relevant information. We modeled the relationship between this dissimilarity matrix as a response and several predictors that we believe could also be associated with the recovery of a more similar set of final loci (MDA, population (i.e., locality), size selection pool and log-transformed number of loci in the final dataset for each sample) using a multivariate distance matrix regression (MDMR) ( Anderson, 2001 ; Mcardle & Anderson, 2001 ) implemented in the R package MDMR v. 0.5.0 ( McArtor, Lubke & Bergeman, 2016 ; McArtor, 2017 , 2018 ). This kind of regression tests the relationship between several variables and a distance matrix, drawing significance from randomization.…”
Section: Methodsmentioning
confidence: 99%
“…All libraries were included in this analysis, without any filter, since even libraries that do not share any locus provide relevant information. We modeled the relationship between this dissimilarity matrix as a response and several predictors that we believe could also be associated with the recovery of a more similar set of final loci (MDA, population (i.e., locality), size selection pool and log-transformed number of loci in the final dataset for each sample) using a multivariate distance matrix regression (MDMR) ( Anderson, 2001 ; Mcardle & Anderson, 2001 ) implemented in the R package MDMR v. 0.5.0 ( McArtor, Lubke & Bergeman, 2016 ; McArtor, 2017 , 2018 ). This kind of regression tests the relationship between several variables and a distance matrix, drawing significance from randomization.…”
Section: Methodsmentioning
confidence: 99%
“…We used multivariate distance matrix regression (MDMR; Anderson, 2001 ; McArdle and Anderson, 2001 ; McArtor et al, 2017 ) to test for the effect of each environmental variable on both observed dissimilarity and dissimilarity deviation. MDMR is very similar to the widely used ordination method Redundancy Analysis.…”
Section: Methodsmentioning
confidence: 99%
“…By design, this novelty index is not effective for other patterns such as gradual or seasonal changes. One promising approach to analyse multiple patterns and covariates simultaneously are multivariate distance matrix regressions (McArtor, Lubke, & Bergeman, ). This approach can test continuous as well as factorial predictors for distance matrices.…”
Section: Discussionmentioning
confidence: 99%